IMPLEMENTASI PEMBELAJARAN KONTEKSTUAL UNTUK MENINGKATKAN LITERASI NUMERASI DAN KEMAMPUAN BERPIKIR KRITIS SISWA - S, Putriyani; parman, Suparman; Azzahrah, Nayla; Iqbal, Muhammad (Diklat Review : Jurnal manajemen pendidikan dan pelatihan, 2025)
Abstract: This research is motivated by the low numeracy literacy and critical thinking skills of junior high school (MTs) students in Enrekang Regency, who are still oriented towards memorization and have not yet connected concepts to real-life contexts. The urgency of this research is to find meaningful and relevant learning strategies that address the local agrarian characteristics of Enrekang. The goal is to describe the implementation of contextual teaching and learning (CTL) in improving students' numeracy literacy and critical thinking skills. This research used a descriptive qualitative approach, conducted over three months at one MTs in Enrekang Regency, with key informants selected purposively as teachers and students. Data were collected through observation, semi-structured interviews, and documentation. Data were then analyzed using the interactive model of Miles, Huberman, and Saldaña, which includes data reduction, data display, and conclusion drawing. Data validity was ensured through triangulation of sources and techniques, member checking, and an audit trail. The results indicate that CTL is effective in increasing student participation, numerical reasoning, and critical reflection.